PENERAPAN MODEL PROJECT BASED LEARNING MENGGUNAKAN CLASS DOJO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XII MULTIMEDIA PADA MATA PELAJARAN DESAIN MEDIA INTERAKTIF DI SMK NEGERI 1 JAPARA: Application Of Project Based Learning Model Using Class Dojo To Improve Learning Outcomes Of Class XII Multimedia Students In Interactive Media Design Subjects At SMK Negeri 1 Japara - Ahmad Fajri Lutfi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This study aims to: (1) determine the learning outcomes of class XII Multimedia students before using the Project Based Learning model using ClassDojo on the subject of Interactive Media Design students at SMK Negeri 1 Japara. (2) Knowing the learning outcomes of class XII Multimedia students after using the Project Based Learning model using ClassDojo on the subject of Interactive Media Design students at SMK Negeri 1 Japara. (3) Knowing the differences in student learning outcomes of class XII Multimedia using the Project Based Learning model with Class Dojo and student learning outcomes using the Discovery Learning model. The respondents of this study were students of class XII Multimedia at SMK Negeri 1 Japara, held in May-July 2021. Using the Nonequivalent Control Group Pretest-Posttest Design method, which is using a test given after the learning process (post test) with the subject of the Experiment class. The design of this study explains that there are two research groups, namely the Experimental Group (EC) and Control Group (KK). The analysis technique used is the Homogeneity Test, Normality Test, and Independent Sample t Test, using SPSS 25 with a level of a = 0.05. than the Discovery Learning model on the learning outcomes of class XII Multimedia students in the subject of Interactive Media Design at SMK Negeri 1 Japara.